Persepsi masyarakat terhadap program pengimarahan masjid di Negeri Pahang: satu analisis = The community’s perception towards the mosque activities programs in Pahang: an analysis - Azlan, Abd. Rahman; Rashidi, Abbas (Global Academic Excellence, Kota Bharu, Kelantan, 2018)
This study was conducted to find out the perception of the community towards the activities program of the mosque in the state of Pahang. A total of 30 respondents were selected in this study consisting of 18 men and 12 women. The methodology of this study uses a mixed method, qualitative and quantitative methods. Data were analyzed using Statistical Package for Social Sciences (SPSS) version 19.0 for the mean, standard deviation and Pearson Correlation. The findings showed that the perception of the community towards religious class in the mosque, the mosque management and the speakers, was generally high achievement. Meanwhile, the result showed that there was a moderate but significant relationship between the presence of people to the mosque and the speaker's personality. Lastly, the result showed that there was a moderate but significant relationship between the presences of people to the mosque with daily lecture as well. In conclusion, this study showed that there was a significant correlation between people (jamaah) and the activities program in the mosque.